Extension in Banana Flour Production as an Effort to Diversify Banana-Based Products in Pakuan Village - Pawestri, Setyaning; Siska Cicilia; Ahmad Alamsyah; Dody Handito; Mutia Nur Kholisah; Sari Oktaviana; Eka Partiwi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Pakuan Village, located in Narmada District, boasts an impressive annual banana production of up to 1.62 tons per hectare. Despite this high potential for banana yields, the development of banana-based products remains limited to banana chips and sale pisang. One significant challenge MSMEs face in Pakuan Village is the lack of applied food production technology. To address this issue, an initiative has been launched to diversify products by transforming unripe Mas Bali bananas into banana flour. This effort aims to add value to banana products while fostering creativity among MSMEs and enhancing their income through banana-based processed goods. Participants were provided with knowledge about the nutritional benefits of bananas and the proper methods for making and storing banana flour. The attendees included members of the Family Welfare and Empowerment (PKK) and the Pokdarwis (Tourism Awareness Group) of Pakuan. It is hoped that the innovation of processed banana flour from unripe Mas Bali bananas will contribute to developing businesses based on local commodities and create opportunities for market penetration.